Comparison of a video to a pictorial brochure in improving HIV/AIDS and HIV testing knowledge and increasing HIV testing motivation and behavioral skills among adult emergency department patients. Issue 3 (20th March 2020) - Merchant, Roland C.; Marks, Sarah J.; Clark, Melissa A.; Carey, Michael P.; Liu, Tao
Abstract: Objectives: We sought to determine if a pictorial brochure improves HIV/AIDS and HIV testing knowledge and increases HIV testing motivation and behavioral skills as well as a video among adult emergency department patients, regardless of language spoken and health literacy level. Methods: ED patients were stratified by primary language spoken (English or Spanish) and health literacy level (lower or higher) and randomly assigned to watch the study video or review the content‐matched pictorial brochure. HIV/AIDS and HIV testing knowledge, motivation for HIV testing, and behavioral skills for HIV testing were assessed using study instruments before and after watching the video or reviewing the pictorial brochure. Results: Of the 712 English‐ and 655 Spanish‐speaking ED patients, HIV/AIDS and HIV testing knowledge improved more among participants in the video than the pictorial brochure arm (∆ 0.43; 95% confidence interval [CI]: 0.07, 0.79). This improvement was more pronounced among those with lower (∆ 0.60; 95% CI: 0.06, 1.13) than higher health literacy (∆ 0.27; 95% CI: −0.22, 0.76). HIV testing motivation was high before the intervention and did not increase differentially between arms. Confidence in recognizing when to be tested for HIV was slightly greater in the video than pictorial brochure arm (∆ 0.15; 95% CI: 0.01, 0.28), but did not differ by language spoken or health literacy level. Conclusions: A video improved HIV/AIDS and HIV testing knowledge slightly more than a pictorial brochure. Other considerations (eg, patient volume, staffing, space, and video access) should guide EDs on how best to provide information about HIV testing to ED patients.